2022
DOI: 10.1002/adom.202200695
|View full text |Cite
|
Sign up to set email alerts
|

On the Response Speed of Narrowband Organic Optical Upconversion Devices

Abstract: and are still cost prohibitive for most consumer and low-end applications. In addition, due to the broadband absorption of inorganic semiconductors, spectrally selective detection is not possible without attached optical filters.As an alternative approach, optical upconversion devices have been developed that directly convert NIR light into visible light. These devices are also denoted as upconversion photodetector, [9] upconversion display/imager, [10,11] or upconversion light-emitting diode. [12] The basic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…For example, Hu et al. ( 44 ) recently demonstrated a η p-p of 0.16% with an EQE product of 0.29% from the OPD (10%) and OLED (2.89%) subunits. Yang et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hu et al. ( 44 ) recently demonstrated a η p-p of 0.16% with an EQE product of 0.29% from the OPD (10%) and OLED (2.89%) subunits. Yang et al.…”
Section: Resultsmentioning
confidence: 99%
“…The upconversion performance can be estimated by the EQE product of the infrared photodetector and the LED, respectively, or as a whole (43). For example, Hu et al (44) recently demonstrated a η p-p of 0.16% with an EQE product of 0.29% from the OPD (10%) and OLED (2.89%) subunits. Yang et al (12) achieved a record-high η p-p of 29.6% with an EQE of 61.7% from the CGL and an ultrahigh EQE of 50% from the tandem OLED.…”
Section: Infrared Visualizationmentioning
confidence: 99%
“…The traditional method uses a broadband photodetector combined with an optical filter, which is bulky in size and makes the system complex. Narrowband photoresponse can be realized through several strategies such as using narrow absorption active layers, , charge collection narrowing, self-filtering, electron-donating amine-interlayer-induced doping, and enhanced charge transfer state absorption by optical resonance . An innovative design of a tunable narrowband photoresponse has been realized by the combination of a Fabry–Perot cavity and a broadband organic detector .…”
Section: Infrared Detector Designsmentioning
confidence: 99%
“…As a result, the OPD with a device structure of ITO/TiO 2 /Jcy/MoO 3 /Ag delivered an EQE at 990 nm of 12% at –2 V (Figure 6d) and a fast responding speed with a f ‐3dB of 50 kHz. [ 73 ]…”
Section: Development Of Polymethine‐based Nir Opdsmentioning
confidence: 99%
“…Experimental results showed that the OUC device achieved a maximum P2PCE of 0.61% at 10 V under 830 nm NIR light excitation, a high luminance leveled off at 670 cd·m −2 beyond ~6 V and the maximum luminance on/off ratio of 4211 at 5 V. Shortly after, this group further reported two high image‐contrast, narrowband OUCs by combining J‐aggregated Jcy‐based OPD with a fluorescent poly ( para ‐phenylene vinylene) copolymer (Super Yellow, SY)‐based OLED and a host‐guest phosphorescent Ir(ppy) 3 OLED, respectively. [ 73 ] In this type of OUCs, a two‐layer film was inserted as the EBL to suppress the dark current substantially, resulting in high luminance on/off ratios (~10 5 ). Both of OUCs showed high visible transmission of over 85% for the full OUC stacks and small reabsorption of emitted light.…”
Section: Emerging Applications Of Polymethine‐based Nir Opdsmentioning
confidence: 99%